Combined Metallomics/Transcriptomics Profiling Reveals a Major Role for Metals in Wound Repair - Wilkinson, Holly N.; Guinn, Barbara-Ann; Hardman, Matthew J. (Frontiers in Cell and Developmental Biology, 2021)
Endogenous metals are required for all life, orchestrating the action of diverse cellular processes that are crucial for tissue function. The dynamic wound healing response is underpinned by a plethora of such cellular behaviours, occurring in a time-dependent manner. However, the importance of endogenous metals for cutaneous repair remains largely unexplored. Here we combine ICP-MS with tissue-level RNA-sequencing to reveal profound changes in a number of metals, and corresponding metal-regulated genes, across temporal healing in mice. Wound calcium, magnesium, iron, copper and manganese are elevated at 7 days post-wounding, while magnesium, iron, aluminium, manganese and cobalt increase at 14 days post-wounding. At the level of transcription, wound-induced pathways are independently highly enriched for metal-regulated genes, and vice versa. Moreover, specific metals are linked to distinct wound-induced biological processes and converge on key transcriptional regulators in mice and humans. Finally, we reveal a potential role for one newly identified transcriptional regulator, TNF, in calcium-induced epidermal differentiation. Together, these data highlight potential new and diverse roles for metals in cutaneous wound repair, paving the way for further studies to elucidate the contribution of metals to cellular processes in the repair of skin and other tissues.